Pitfalls in Retinal OCT Imaging. Issue 1 (2017) - Schmitz-Valckenberg, Steffen; Brinkmann, Christian Karl; Heimes, Britta; Liakopoulos, Sandra; Spital, Georg; Holz, Frank Gerhard; Fleckenstein, Monika
Optical coherence tomography (OCT) imaging plays an important role in the management of retinal diseases. However, limitations and pitfalls should be taken into consideration when applying this noninvasive imaging technology. The aim of this review is to discuss several possible sources of error in the conduct and interpretation of OCT imaging.